2021
DOI: 10.1108/vjikms-09-2020-0165
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership: an antecedent for organizational effectiveness in Indian banks

Abstract: Purpose The purpose of this study is to empirically explore the connection between transformational leadership (TL) and organizational effectiveness (OE). Also, the paper looks at the mediating impact of employee innovative behaviour (EIB) and the moderating effect of knowledge sharing (KS) on the aforementioned association. Design/methodology/approach The respondents included 410 bank employees from North India. The mediating effect of EIB and moderating effect of KS was explored by plug-in for SPSS, PROCES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 120 publications
1
4
0
Order By: Relevance
“…First, we found a positive association between transformational leadership style and IWB, exhibited by the leader and the employees, respectively ( H 1 ). The study’s findings are consistent with previous studies, which found that transformational leadership style positively impacts employees’ IWB by providing a culture where employees can freely suggest and implement innovative ideas and facilitate overall organisational effectiveness (Jung et al, 2003; Tayal et al, 2021). Innovative organisational behaviour would improve service quality in the banking context and be instrumental in various non-banking services like investment advice (Parameswar & Dhir, 2017).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…First, we found a positive association between transformational leadership style and IWB, exhibited by the leader and the employees, respectively ( H 1 ). The study’s findings are consistent with previous studies, which found that transformational leadership style positively impacts employees’ IWB by providing a culture where employees can freely suggest and implement innovative ideas and facilitate overall organisational effectiveness (Jung et al, 2003; Tayal et al, 2021). Innovative organisational behaviour would improve service quality in the banking context and be instrumental in various non-banking services like investment advice (Parameswar & Dhir, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…The leaders promote a culture where employees are motivated to discuss innovative and new ideas openly. Tayal et al (2021), in their study of the Indian banking sector, found a positive relationship between transformational leadership and employees' IWB. They also established the mediating role of employees' IWB between transformational leadership and organisational effectiveness.…”
Section: Transformational Leadership and Innovative Work Behaviourmentioning
confidence: 96%
“…KS possess a capability to moderate the effectiveness of the organization. OE is the outcome of KS (Tayal et al, 2021). EC, on the other hand, are heavily influenced by KS.…”
Section: Knowledge Sharingmentioning
confidence: 99%
“…These approaches converge by recognizing the need to improve the customer experience, ensure information transparency, and promote the adoption of innovative technologies in the banking sector [15]. However, customer satisfaction and loyalty in financial institutions are influenced by several factors, such as service quality, product knowledge, and employee skills.…”
Section: Banking Customers In Era 40mentioning
confidence: 99%